Papillary thyroid carcinoma tall cell variant shares accumulation of mitochondria, mitochondrial DNA mutations, and loss of oxidative phosphorylation complex I integrity with oncocytic tumors. (17th November 2021) - Tsybrovskyy, Oleksiy; De Luise, Monica; de Biase, Dario; Caporali, Leonardo; Fiorini, Claudio; Gasparre, Giuseppe; Carelli, Valerio; Hackl, Dominik; Imamovic, Larisa; Haim, Silke; Sobrinho‐Simões, Manuel; Tallini, Giovanni
Abstract: Papillary thyroid carcinoma tall cell variant (PTC‐TCV), a form of PTC regarded as an aggressive subtype, shares several morphologic features with oncocytic tumors. Pathogenic homoplasmic/highly heteroplasmic somatic mitochondrial DNA (mtDNA) mutations, usually affecting oxidative phosphorylation (OXPHOS) complex I subunits, are hallmarks of oncocytic cells. To clarify the relationship between PTC‐TCV and oncocytic thyroid tumors, 17 PTC‐TCV and 16 PTC non‐TCV controls (cPTC) were subjected to: (1) transmission electron microscopy (TEM) to assess mitochondria accumulation, (2) next‐generation sequencing to analyze mtDNA and nuclear genes frequently mutated in thyroid carcinoma, and (3) immunohistochemistry (IHC) for prohibitin and complex I subunit NDUFS4 to evaluate OXPHOS integrity. TEM showed replacement of cytoplasm by mitochondria in PTC‐TCV but not in cPTC cells. All 17 PTC‐TCV had at least one mtDNA mutation, totaling 21 mutations; 3/16 cPTC (19%) had mtDNA mutations ( p  < 0.001). PTC‐TCV mtDNA mutations were homoplasmic/highly heteroplasmic, 16/21 (76%) mapping within mtDNA‐encoded complex I subunits. MtDNA mutations in cPTC were homoplasmic in 2 cases and at low heteroplasmy in the third case, 2/3 mapping to mtDNA‐encoded complex I subunits; 2/3 cPTC with mtDNA mutations had small tall cell subpopulations. PTC‐TCV showed strong prohibitin expression and cPTC low‐level expression, consistent with massive and limited mitochondrial content, respectively. All 17 PTC‐TCV showed NDUFS4 loss (partial or complete) and 3 of 16 cPTC (19%) had (partial) NDUFS4 loss, consistent with lack of complex I integrity in PTC‐TCV ( p  < 0.001). IHC loss of NDUFS4 was associated with mtDNA mutations ( p  < 0.001). Four BRAF V600E mutated PTCs had loss of NDUSF4 expression limited to neoplastic cell subpopulations with tall cell features, indicating that PTCs first acquire BRAF V600E and then mtDNA mutations. Similar to oncocytic thyroid tumors, PTC‐TCV is characterized by mtDNA mutations, massive accumulation of mitochondria, and loss of OXPHOS integrity. IHC loss of NDUFS‐4 can be used as a surrogate marker for OXPHOS disruption and to reliably diagnose PTC‐TCV.